Influence of Method and Application Time of Nitrogen on Pest Incidence of Sorghum [Sorghum bicolor (L.) Moench] Genotypes - Raypuriya, Neelesh; Choudhary, R. K.; Swathi, P.; Prajapati, Sunil (International Journal of Bio-resource and Stress Management, 2017)
An experiment was conducted under open field condition in the month of June to December in the year of 2013 at College of Agriculture, Indore, R.V.S.K.V.V. (M.P.), India. Nitrogen application time and cultivars were significantly effective but their interaction was non-significantly effective for incidence of insect pest (exception of ear head bug), whereas both factor and interaction were significantly effective to growth parameter. CSV20 was recorded with significantly lowest incidence of pests and maximum for growth parameters in comparison to CSH16 in nitrogen application time treatment N1: 50% at sowing+50% at 30 DAS maximum incidence of Shoot fly (57.87% and 64.39%) at 14 and 21 days, while minimum in stem borer dead hearts (41.15%) at 45 DAE, Ear head pests (3.75 bug & 3.0 worm) at milk stage, N2: 50% at sowing+25% at 30 DAS+25% at boot leaf stage was found highest height of plant (182.33 cm.), N3: 25% at sowing+50% at 30 DAS+25% at BLS has been recorded higher stem borer dead hearts (51.42%), N4: 25% at sowing+50% at 30 DAS+15% at BLS+10% at grain filling stage reported maximum ear head pests (6.78% and 4.27%), treatment N5: 25% at sowing+45% at 30 DAS+5% foliar spray at 45 DAS+15% BLS+10% GFS) recorded minimum incidence of shoot fly (43.85% and 51.12%). Among the treatment maximum number of grains ear head-1 was recorded in the treatment N4, (2369.33) at GFS and N5 (2111.17) at GFS with and higher yield plot-1 and stover yield was recorded in the treatment N5 (2.79 kg and 2.88 kg) respectively.